2022
DOI: 10.3389/fphys.2022.1005698
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT scan for the screening of air anomalies at risk of pulmonary barotrauma for the initial medical assessment of fitness to dive in a military population

Abstract: Introduction: The presence of intra-pulmonary air lesions such as cysts, blebs and emphysema bullae, predisposes to pulmonary barotrauma during pressure variations, especially during underwater diving activities. These rare accidents can have dramatic consequences. Chest radiography has long been the baseline examination for the detection of respiratory pathologies in occupational medicine. It has been replaced since 2018 by the thoracic CT scan for military diving fitness in France. The objective of this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Therefore, previous investigations into the prevalence of bullae mainly originate from the field of diving medicine ( de Bakker et al, 2020a ; Bonnemaison et al, 2022 ; Weaver et al, 2022 ). Given their potential connection to PBT, the interest of the field of diving medicine in this topic is no surprise ( Germonpré et al, 2008 ; Goffinet and Simpson, 2019 ; de Bakker et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, previous investigations into the prevalence of bullae mainly originate from the field of diving medicine ( de Bakker et al, 2020a ; Bonnemaison et al, 2022 ; Weaver et al, 2022 ). Given their potential connection to PBT, the interest of the field of diving medicine in this topic is no surprise ( Germonpré et al, 2008 ; Goffinet and Simpson, 2019 ; de Bakker et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…In numerous standards, chest X-ray is still mentioned to exclude clinically relevant pulmonary pathology, but computed tomography (CT) for structural analysis of the pulmonary system has been shown a highly superior imaging technique ( Health and Safety Executive, 2023 ). However, higher-resolution CT scans in healthy individuals can uncover incidental findings of unknown clinical significance, raising concerns for its routine use in fitness to dive assessments in the general population ( Wingelaar et al, 2020 ; Bonnemaison et al, 2022 ). A forensic ( post mortem ) CT study in 130 adults without pulmonary injuries revealed that 33.8% of subjects had bullae/blebs ( de Bakker et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these observations, in a recent study, chest CT scans were performed in 76 young (median age 25 years) military diving candidates with no known lung pathology. An isolated pulmonary cyst was identified in one individual, and that person was subsequently deemed unfit to dive [ 17 ]. Nonetheless, the high frequency of pulmonary cysts in the general population combined with the large number of scuba divers and the limited number of fatal accidents indicates that the absolute risk of fatality due to lung cysts is likely to be low.…”
Section: Discussionmentioning
confidence: 99%
“…However, since pulmonary lesions have been associated with an increased risk of pulmonary barotrauma, one of the major causes of scuba diving-related fatalities, caution is in our opinion still warranted in patients with BHD until larger cohort studies are available. Based on the risks associated with lung lesions during scuba diving, it has been previously discussed to perform a chest CT as part of the medical certification of divers [ 17 ], because lung cysts are usually asymptomatic and will not be detected during routine medical diving screening. However, screening of all divers by chest CT was considered to be impractical and not cost-effective and therefore suggested as an option for professional divers [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%